Immense Power in a Tiny Package: Wearables Based on Electrical Muscle Stimulation - Lopes, Pedro; Baudisch, Patrick (IEEE pervasive computing, 2017)
Electrical muscle stimulation (EMS) devices have been used in rehabilitation medicine since the 1960s to regenerate lost motor functions, but, more recently, researchers have started to experiment with EMS to create interactive systems. EMS miniaturizes well, easily lending itself to pervasive computing use cases--particularly those involving mobile and wearable devices. As the authors discuss, EMS provides researchers with the technical means to create devices even smaller than current wearable devices. The authors illustrate this by comparing some of their own prototypes based on EMS with traditional approaches involving mechanical actuators.